Drag Force Coefficient for Various Shapes of Cooling Tower Subjected to Wind Load - Krishna Kumar, S; Pravin Kumar, S (International Journal of Computer Sciences and Engineering, 2025)
Hyperbolic cooling tower is a tall structure with thin shells subjected to dead load, wind load and ground motion. In absence of ground motion, wind becomes the major factor. In this study three models with different profiles were modelled using Catia and analyzed in Ansys to find drag force and drag coefficient. The results of the models were compared with conventional hyperbolic profile cooling tower. It was found that CT – 2 (Part of the structure has hyperbolic profile and other part is parallel to the vertical axis) has less effect due to wind. The Drag Coefficient of CT – 3 is least when compared to other models but projected area is high, which leads to increase in drag force. The drag force of CT – 2 is 83.2% of conventional cooling tower. Therefore CT – 2 profile is recommended when compared to other profiles.